Image Caption Generation Model Based on Object Detector - Poghosyan, Aghasi S.; Sarukhanyan, Hakob G. (Mathematical Problems of Computer Science, 2021)
Automated semantic information extraction from the image is a difficult task. There are works, which can extract image caption or object names and their coordinates. This work presents object detection and automated caption generation implemented via a single model. We have built an image caption generation model on top of object detection model. We have added extra layers on object detector to increase caption generator performance. We have developed a single model that can detect objects, localize them and generate image caption via natural language.